Analisis Strategi Persaingan Untuk Meningkatkan Penjualan Usaha Sambal Cumi dan Paru By Dapoer Zambal - Rofik, Oktavio Mi’roj; Cahyani, Linda Ratna Fitria; Widodo, Ricia Ratri; Rahmawati, Dewi Cantika; Ningsih , Ajeng Kusuma; Wahib, Moh (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
Sambal Cumi and Paru by Dapoer Zambal is a new instant food business established in 2023. Not many people know about this business because it is still very new. In addition, there are many competitors working on the same business and are already successful. This study was conducted to determine whether the right competitive strategy can increase the sales of Dapoer Zambal's Sambal Cumi and Paru. For this study, a strengths, weaknesses, opportunities, and threats approach was used as a descriptive qualitative methodology. The analysis results show that improving customer service and adding new menu variations are the most effective competitive approaches to increase sales.